BIOETIKA PENELITIAN KUALITAS AIR DI PEMUKIMAN JALAN KALI BRANTAS, KARANG SUKUN, KOTA MATARAM - Ni Made Pujiastiti Hapsari; Karmila Fajriah; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
The quality of clean water in dense urban settlements often fails to meet health standards, particularly in microbiological aspects. This study aims to analyze the quality of clean water in the Jalan Kali Brantas area, Karang Sukun Village, Mataram City, using the membrane filter method, while simultaneously examining the application of bioethical principles at each stage of the research. A descriptive-analytical approach was employed with purposive sampling from dug wells and other water sources in the area. Laboratory results revealed that the majority of samples contained Escherichia coli bacteria and total coliform counts exceeding the quality standards set by Minister of Health Regulation No. 2 of 2023. The bioethical review affirms that the principles of autonomy, beneficence, non-maleficence, and justice must be substantively integrated into the design and implementation of environmental health research, rather than treated as mere administrative formalities. This study is expected to encourage improvements in local clean water management policy and serve as a model for ethical and accountable participatory research.